Rapid postural improvement in mixed diagnosis of recurrent vestibulopathy and posterior BPPV: a case study - Zuber Ahmadi, Muhammad Munzir; Zainun, Zuraida; Hashim, Sabarisah (Faculty of Medicine, 2026)
Benign paroxysmal positional vertigo (BPPV) is a condition caused by otoconia that cause spinning. Recurrent vestibulopathy is characterized by several episodes of vertigo lasting minutes to hours, which last longer than six months and are devoid of neurological or auditory symptoms. The triggering factors for mixed BPPV and recurrent vestibulopathy include head trauma, inner ear disease, and prolonged immobilization following cerebrovascular infarction. In this case, we evaluated the improvement of recurrent vestibulopathy and posterior BPPV case using BPPV manaeuvre and Intensive Balance Rehabilitation specifically looking at postural control. A 51-year-old female patient, with a history of asthma, allergic rhinitis, migraine, and vertigo for three years was diagnosed to have recurrent chronic vestibulopathy. Vestibular Rehabilitation using the Bal Ex exercise was applied to promote adaptation to and substitution for various aspects of deficits related to a wide variety of balance disorders.